Role of State Government in Safety of Women in the Chhattisgarh State: Examining the Role of State Governments in Ensuring Women's Safety in Chhattisgarh (Journal of Advances and Scholarly Researches in Allied Education, 2022)
In today’s era we talk about modernisation where we want the women of our society to be self- dependent they should live their lives with full freedom so that they can easily run their life but in this we somewhere has forgotten about the safety of women along with the freedom some or the other way they are not safe this modernisation has given them respect in the society, a place in the society where they have freedom to speak, represent their thoughts and feeling but safety is still missing , still they are struggling for their safety. It is the duty of the society as well as the state to take proper care of the safety of the women. Where we teach them about to be self-dependent there is need to make them also learn about the self-defence so that they can protect themselves in the situation where they feel they are not safe. Now – a-days we see so many cases of rape, kidnapping, eve teasing all this are becoming very common and frequent now -a-days which is much necessary to be taken care off. Thus, this paper focuses on the women safety and what role state governments play for the safety of the women. This is about one of the missions named “Rail Garjana” which is an initiative taken by Mrs. Harsha Sahu (An International Karate Player) along with the RPF (Railway police force of CG) and the Government of Chhattisgarh in this mission Mrs. Harsha Sahu with the help of RPF is making women learn self-defence and how they can safe their life and make themselves safe.